Dictionary of finance and banking. (Oxford, UK Oxford University Press, 2018)
With over 5,500 - including 150 new - accessible entries, this sixth edition of the bestselling Dictionary of Finance and Banking has been fully revised and updated to take into account the ever-developing financial landscape of the last five years. This comprehensive A-Z defines terms from all aspects of personal and international finance, including money markets, private investments and borrowing, central banking, foreign exchanges, monetary policy, and public and government finance. Now with expanded international coverage to reflect the on-going globalization of financial markets and the growing importance of development finance, with new entries such as village banking, Islamic Development Bank, and M-Pesa. Quick links for additional online resources relating to the field can also be found on the companion website to expand reading and delve deeper into the world of finance and banking. With clear and accessible definitions, this jargon-free dictionary is a companion volume to the other financial titles in this bestselling series (A Dictionary of Business and Management, A Dictionary of Accounting, and A Dictionary of Economics), and provides accurate and valuable information for students, practitioners, private investors, and readers of the financial pages alike.
Previous edition: 2008, edited by Jonathan Law.
Keywords: Finance -- Dictionaries; Banks and banking -- Dictionaries; Banks and banking; Finance; Dictionaries